2023
DOI: 10.1038/s41598-023-31312-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of prognosis in patients with severe COVID-19 pneumonia using CT score by emergency physicians: a single-center retrospective study

Abstract: We aimed to develop a method to determine the CT score that can be easily obtained from CT images and examine its prognostic value for severe COVID pneumonia. Patients with COVID pneumonia who required ventilatory management by intubation were included. CT score was based on anatomical information in axial CT images and were divided into three sections of height from the apex to the bottom. The extent of pneumonia in each section was rated from 0 to 5 and summed. The primary outcome was the prediction of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…CT-SS can indicate the extent to which the COVID-19 pneumonia image is occupied, and the value of CT-SS in predicting the prognosis of COVID-19 patients has been reported by several studies [9][10][11][12][13][14][34][35]. Similar to a moderate predictive value of CT-SS alone with a AUC of 0.718 for in-hospital mortality in patients with severe COVID-19 pneumonia [9], our current study also showed that the AUC of CT-SS was only 0.790 for in-hospital mortality of COVID-19 patients. The unsatisfactory predictive value of CT-SS for COVID-19 outcomes is related to its inevitable limitations.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…CT-SS can indicate the extent to which the COVID-19 pneumonia image is occupied, and the value of CT-SS in predicting the prognosis of COVID-19 patients has been reported by several studies [9][10][11][12][13][14][34][35]. Similar to a moderate predictive value of CT-SS alone with a AUC of 0.718 for in-hospital mortality in patients with severe COVID-19 pneumonia [9], our current study also showed that the AUC of CT-SS was only 0.790 for in-hospital mortality of COVID-19 patients. The unsatisfactory predictive value of CT-SS for COVID-19 outcomes is related to its inevitable limitations.…”
Section: Discussionmentioning
confidence: 96%
“…Chest CT severity score calculation CT-SS was performed using the semiquantitative method [9,19], which was also shown in Fig. 1.…”
Section: Data Collection and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a Picture Archiving and Communication System (PACS; EV Insite version 3.11.1.500; PSP Corporation, Japan), three radiologists with 9, 10, and 14 years of experience performed consensus interpretations blinded to the patients’ clinical information. The evaluators assessed the presence of the following CT patterns; consolidation, ground-glass opacities (focal, multifocal, diffuse), mosaic attenuation patterns (hypoattenuating and hyperattenuating areas), perilobular consolidation (organizing pneumonia-like pattern), reticulations, architectural distortion, honeycombing, traction bronchiectasis, pneumatocele, curvilinear lines, nodules, and pleural thickening or pleural effusion [ 15 ]. Additional findings were annotated separately.…”
Section: Methodsmentioning
confidence: 99%
“…Most SARS-CoV-2-infected patients develop only a mild, self-limiting disease. However, approximately 15–20% of COVID-19 patients develop severe pneumonia, and 5–10% need intensive care treatment [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%